2013
DOI: 10.1007/s00199-013-0768-9
|View full text |Cite
|
Sign up to set email alerts
|

Taxing pollution: agglomeration and welfare consequences

Abstract: This paper demonstrates that a pollution tax with a …xed cost component may lead, by itself, to segregation between clean and dirty …rms without heterogeneous preferences or increasing returns. We construct a simple model with two locations and two industries (clean and dirty) where pollution is a by-product of dirty good manufacturing. Under proper assumptions, a completely strati…ed con…guration with all dirty …rms clustering in one city emerges as the only equilibrium outcome when there is a …xed cost compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…This may stimulate enterprises in agglomeration regions to adopt more advanced, environmentally friendly production technologies, which can effectively reduce pollutant emissions (Baomin et al, 2012;Pessoa, 2014;Galliano et al, 2015) [71][72][73]. Second, the production activities of the same industry within a specialized cluster typically generate the same or similar pollutants; therefore, public pollution control facilities can realize specialized operations and create a scale effect (Berliant, 2013;Costantini, 2014) [74,75]. Third, the scale effect of manufacturing agglomeration can increase residential income and fiscal revenue through improved regional labor productivity.…”
Section: Results Of the Panel Threshold Regressionmentioning
confidence: 99%
“…This may stimulate enterprises in agglomeration regions to adopt more advanced, environmentally friendly production technologies, which can effectively reduce pollutant emissions (Baomin et al, 2012;Pessoa, 2014;Galliano et al, 2015) [71][72][73]. Second, the production activities of the same industry within a specialized cluster typically generate the same or similar pollutants; therefore, public pollution control facilities can realize specialized operations and create a scale effect (Berliant, 2013;Costantini, 2014) [74,75]. Third, the scale effect of manufacturing agglomeration can increase residential income and fiscal revenue through improved regional labor productivity.…”
Section: Results Of the Panel Threshold Regressionmentioning
confidence: 99%
“…Previous studies have identified the determinants of pollution as economic development, environmental regulations, political transparency, R&D inputs, and ownership [8,18,19]. Environmental regulations have received the most attention [20][21][22], and the effects of industrial agglomeration and technological inputs have also been explored [3,7,8,23]. However, insufficient attention has been paid to the spillover channels among various cities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This reduction has also led families to substitute educational time for leisure time, which ultimately increases the long-term growth rates [31]. Besides, Berliant modified Futagam's model to analyze the impact of fiscal policy on long-term growth [32]. He also proved that pollution tax has a positive effect on economic growth because higher pollution tax revenue will increase the stock of public capital and thus will have a positive effect on growth.…”
Section: The Effect Of Economic Growthmentioning
confidence: 99%